Women and stroke: disparities in clinical presentation, severity, and short- and long-term outcomes - Naveed, Hiba; Almasri, Muna; Kazani, Bahram; Nauman, Areej; Akhtar, Naveed; Singh, Rajvir; Kamran, Saadat; Al Jerdi, Salman; Thermalingem, Sathvika; Shuaib, Ashfaq (Frontiers in Neurology, 2023)
Objectives There are limited data from the Middle East on sex-related differences in short- and long-term stroke outcomes. We present 8 years of experience based on the Qatar stroke database. Setting The Qatar stroke database prospectively collects data on all stroke patients admitted to Hamad General Hospital. For this study, we compared female and male acute ischemic stroke patients on their characteristics at admission, short-term outcomes [modified Rankin Scale (mRS) score], and long-term outcomes [incidence of major adverse cardiovascular events (MACEs)]. Participants A total of 7,300 patients [F: 1,406 (19.3%), M: 5,894 (80.7%); mean age 55.1 ± 13.3 (F: 61.6 ± 15.1, M: 53.5 ± 12.3; p < 0.001)] were admitted with acute ischemic stroke. Results Significantly fewer women presented within 4.5 h of onset (F: 29% vs. M: 32.8%; p = 0.01). Although women were more likely to experience severe stroke (NIHSS >10; F: 19.9% vs. M: 14.5%; p < 0.001), fewer were treated with thrombolysis (F: 9.8% vs. M: 12.1%; p = 0.02). Women experienced more medical complications (F: 11.7% vs. M: 7.4%; p < 0.001) and tended to have a more prolonged length of stay in the hospital (F: 6.4 ± 7.6 days vs. M: 5.5 ± 6.8 days; p < 0.001). Primary and secondary outcome measures Good outcomes at 90 days (mRS score of 0–2) were less frequent in women (F: 53.3% vs. M: 71.2%; p < 0.001). Fewer female patients were taking antiplatelets (F: 78% vs. M: 84.8%; p < 0.001) or statins (F: 81.2% vs. M: 85.7%; p < 0.001). Significantly more female patients experienced a MACE (F: 12.6% vs. M: 6.5%; p < 0.001). Conclusion Older age at presentation contributes to poor outcomes following acute stroke in women. Other contributing factors include delays in admission to the hospital, lower rates of thrombolysis, and lower rates of provision of preventative treatments.